2011
DOI: 10.1177/2150135110395409
|View full text |Cite
|
Sign up to set email alerts
|

Results of Balloon Atrial Septostomy as Preparation for Surgical Correction in Transposition of Great Arteries

Abstract: Balloon atrial septostomy (BAS) is a palliative procedure performed in the preoperative management of patients with transposition of great arteries (TGA), to improve the mixing of blood between the 2 systems. This report describes experience at the Clínica Cardiovascular Santa Maria in Medellin, Colombia. Between 2002 and 2010, 22 patients with TGA underwent BAS. Patient age at the time of the procedure was 21 days on average; 68% of patients were male. Average weight was 2.96 kg and interatrial gradient was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this case, the closure of foramen ovale may lead to disabled gas exchange and the development of respiratory failure. Then, atrial septostomy is a suggested life-saving procedure in the majority of neonates with the transposition of great arteries [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the closure of foramen ovale may lead to disabled gas exchange and the development of respiratory failure. Then, atrial septostomy is a suggested life-saving procedure in the majority of neonates with the transposition of great arteries [2,3,4].…”
Section: Introductionmentioning
confidence: 99%